The cosmic ray electron spectrum and its modulation from 1968 through 1972 - Fulks, G.; Meyer, P.; Lheureux, J. (1974)
Over the past five years we have measured the energy spectrum of primary cosmic ray electrons with both a balloon-borne and a satellite absorption spectrometer. All of the balloon flights used identical equipment that was launched each summer from Fort Churchill, Manitoba, Canada. The satellite, OGO-5, has been in an eccentric orbit since March 1968. Together these instruments provide the electron spectrum over a range of energy from 20 MeV to 20 GeV. This wide range and the substantial span of time covered by the measurements permit a detailed study of the solar modulation of electrons. These results are compared with the modulation of the nuclear components as observed by a neutron monitor and interpreted using the cosmic ray transport equation.